2007
DOI: 10.1590/s0103-21002007000200014
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da eficácia da pomada de própolis em portadores de feridas crônicas

Abstract: OBJETIVO: Avaliar a evolução de úlceras crônicas utilizando a terapêutica tópica com a própolis. MÉTODOS: Trata-se de um estudo descritivo onde foram identificadas vinte pessoas com feridas crônicas encaminhadas pelas Unidades Básicas de Saúde do Município de Maringá, Paraná. A análise baseou-se na avaliação e no tempo de cicatrização das feridas, realizada por meio do cálculo do Coeficiente de Correlação de Pearson para verificar a relação entre as medidas médias horizontais, verticais e de profundidades, a e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 2 publications
0
6
0
10
Order By: Relevance
“…In addition, regarding pain felt by people with chronic wounds, all of them reported improvement, even though its level was not assessed by this study. Despite research limitations, authors confirmed the anti-inflammatory and analgesic efficacy of propolis, among other things (11) .…”
Section: Thematic Focus Approachmentioning
confidence: 83%
See 3 more Smart Citations
“…In addition, regarding pain felt by people with chronic wounds, all of them reported improvement, even though its level was not assessed by this study. Despite research limitations, authors confirmed the anti-inflammatory and analgesic efficacy of propolis, among other things (11) .…”
Section: Thematic Focus Approachmentioning
confidence: 83%
“…Martinez Garcia et al (14) ;Duailibe et al (15) Clinical -Antimicrobial action Azevedo et al (4) ;Santos et al (11) ; Lofuto et al (35) Clinical -Therapeutic action in wound healing Peruchi et al (2) ;Park et al (3) ;Vargas et al (5) ; Fernandes Júnior et al (6) ; Silva et al (7) ;Sforcin et al (8) ; Sforcin et al (9) ;Oliveira et al (10) ; Auricchio et al (35) ; Fernandes Júnior et al (17) ;Machado et al (18) ;Longhini et al (19) ;Sawaya et al (20) ;Fernandes et al (21) ;Fernandes Júnior et al ( 22) ; Muli et al (23) ;Gebara et al (24) ;Fernandes Júnior et al (25) ;Bianchini et al (26) ;Gonçales et al (27) ;Dantas et al (28) ; Ayres et al (29) ;Orsi et al (30) ;Orsi et al (31) ;Sforcin et al (32) ;Sforcin et al (33) ;Orsi et al (34) ; Fernandes Júnior et al (36) ;Fernandes et al (37) ; Araújo et al (38) Experimental -Antimicrobial action Rahal et al (16) Experimental -Therapeutic action in wound healing (1) . Another study, which used propolis ointment on 22 chronic wounds, of which 11 were venous ulcers, seven pressure ulcers, two diabetic ulcers, and two post-trauma injuries, found that necrotic tissue was present in 14 (8.2%) during tissue assessment process.…”
Section: Thematic Focus Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…O cuidar de pessoas com lesões na pele tem por desafio o conhecimento dos diversos fatores biológicos, físicos e sociais que envolvem a cicatrização e sua interligação com o processo sáude-doença-cuidado na sua integralidade e a terapêutica com as propriedades da própolis pode colaborar na cicatrização de feridas (SANTOS;VIANA;GAMBA, 2007).…”
Section: Wakita E Hernandes (2019)unclassified